Development of Problem-Solving-Based Flipbook Learning Media to Improve Science Learning Outcomes of Fifth Grade Elementary School Students - Tirtawati, I Gusti Ayu; I Made Citra Wibawa; Putu Ari Dharmayanti (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes of students and the lack of utilization of innovative instructional media remain crucial issues in the learning process for fifth-grade elementary school students. The absence of interactive and contextual media has led to suboptimal learning processes and students' achievement falling short of expected targets. This study aims to analyze, develop, validate, evaluate the practicality, and examine the effectiveness of a problem-solving-based flipbook learning media to improve students’ IPAS (Science, Social, and Environment) learning outcomes. This research employed a Research and Development (R&D) method consisting of planning, development, and product trial stages. The subjects involved 32 fifth-grade students. Data were collected through validation questionnaires, student response questionnaires, and learning achievement tests comprising pre-tests and post-tests. Data were analyzed qualitatively to assess the feasibility of the media and quantitatively using a paired sample t-test to examine its effectiveness. The results indicated that the developed flipbook media achieved very valid qualifications in terms of content and media validity, was highly practical, and significantly improved students’ learning outcomes in IPAS. These findings recommend the use of problem-solving-based flipbook media as an innovative alternative to optimize student-centered learning processes.